Green Pages Philippine agribusiness and food market factbook, 1995-96. (Ortigas, Pasig City Green Leaf Pub., 1995)
A project of the Institute for Agribusiness Development and Policy of the Center for Research and Communication (CRC), this fact book provides information on the Philippine Agribusiness from "conception" to "consumption". This includes farming, food and non-food processing, marketing and distribution of fresh and processed products, and inputs supply.
A valuable and handy reference for people planning to or who are already engaged in agribusiness, this fact book and directory presents useful statistics in analyzing trends in the agribusiness world. The fact book includes statistics on costs (current and fixed), expenditures, exports, imports, sales and consumptions by item and region in the country. The material also features a brief description about every agricultural item, its domestic production, key industry players and prospects on the development of the industry.
Earlier ed. entered under title: Agribusiness Factbook and Directory, 1987-
Fifth ed. entitled : Food and Agribusiness Factbook and Directory.
Keywords: Agriculture -- Philippines -- Handbooks, manual, etc; Agriculture -- Philippines -- Statistics; Farm produce -- Philippines -- Statistics; Produce trade -- Philippines -- Directories; Agricultural industries -- Philippines -- Directories